1997
DOI: 10.1093/brain/120.5.729
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, stability and predictors of outcome of pallidotomy for Parkinson's disease. Six-month follow-up with additional 1-year observations

Abstract: We tested the efficacy, stability and predictors of outcome of unilateral pallidotomy used to treat patients with Parkinson's disease inadequately controlled with pharmacotherapy (IP). The surgical procedure was as simple as possible; we used CT rather than MRI, and we omitted microelectrode recording. We studied 24 patients with IP; 22 of these patients had drug-induced dyskinesias. There was a significant and stable improvement in all the major parkinsonian motor signs in the OFF (medication) state on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 3 publications
4
111
1
1
Order By: Relevance
“…537 Some debate remains with respect to the need for microelectrode guidance, with some arguing it is essential to find the optimal site for the lesion, 538 whereas others argue that the extra needle passes required increase the risk of hemorrhage and that similar results can be obtained without it. 539 There is little information on the efficacy of bilateral pallidotomy, as the procedure is rarely performed because of risk of side effects mentioned earlier.…”
Section: The Observation That Thalamotomy Is So Effective In Amelioramentioning
confidence: 99%
“…537 Some debate remains with respect to the need for microelectrode guidance, with some arguing it is essential to find the optimal site for the lesion, 538 whereas others argue that the extra needle passes required increase the risk of hemorrhage and that similar results can be obtained without it. 539 There is little information on the efficacy of bilateral pallidotomy, as the procedure is rarely performed because of risk of side effects mentioned earlier.…”
Section: The Observation That Thalamotomy Is So Effective In Amelioramentioning
confidence: 99%
“…55 Subthalamic nucleus lesions allow for a reduction in levodopa, whereas levodopa remains practically unchanged after pallidotomy. 88 This advantage is valuable when patients have levodopa-induced hallucinations. Although there are no studies on this matter, STN DBS was recently shown to reduce hallucinations after medication adjustments 172 and could be achieved with STN lesions.…”
Section: Subthalamotomy Versus Other Surgical Treatmentsmentioning
confidence: 99%
“…The growing experience with pallidal lesions for Parkinson's disease shows frequent improvement of all kind of dyskinesias/dystonias, including the ones not related to L-Dopa therapy [3][4][5][6][7][8][9][10][11] . These findings, along with some recent reports of marked improvement in medically refractory dystonias prompted us to evaluate the effectiveness of this procedure in a group of selected patients [12][13][14][15][16] .…”
mentioning
confidence: 99%